Asthma exercise and Buteyko breathing interventions in adolescents: Effects on fitness and exacerbation rates - Laily, Dayang; Rita, Erni; Awalliah, Awaliah; Saba, Iba Supra (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Asthma in adolescents is a global health challenge. Asthma management includes pharmacological and non-pharmacological approaches. Asthma exercises and Buteyko breathing techniques are non-pharmacological therapeutic alternatives. The lifestyle of adolescents who tend to be less physically active becomes a risk factor that increases the incidence and recurrence of asthma. Purpose: To determine the effect of asthma exercises and Buteyko breathing techniques on physical fitness and recurrence in adolescent with asthma. Method: A pre-experimental design with a one group pre-test post-test without control group approach. The sampling technique used total sampling with 33 participants. The statistical test used was the paired sample t-test. Results: The findings revealed a significant effect of the intervention on both physical fitness and asthma recurrence, with a p-value of 0.001. The combination of asthma exercises and Buteyko breathing techniques proved effective in enhancing physical fitness and reducing the frequency of asthma attacks among adolescents. Conclusion: Asthma exercises and Buteyko breathing techniques significantly improve physical fitness and reduce asthma recurrence in adolescents. Suggestion: Schools should integrate these interventions into health programs. Further research with control groups is recommended.